Bond strength evaluation of bulk-fill composites to dentin under different surface treatments = Evaluación de la resistencia adhesiva de las resinas bulk-fill a la dentina con diferentes tratamientos de superficie - Bas, Kazım
Purpose: The aim of this study is to compare the shear bond strength of three high-viscosity bulk-fill composite resins applied as single layers of 4mm thickness and of one microhybrid composite resin applied incrementally with a thickness of 2mm on dentin surfaces prepared with different surface preparation methods. Materials and Methods: A total of 132 caries-free human molars whose dentines had been exposed were used. Three groups, each containing 44 teeth, were formed. The acid group was etched with 32% phosphoric acid; laser group was etched with Er, Cr; YSGG laser and the control group was prepared with silicon carbid paper. Following the application of bonding agent, composite resin materials were applied on teeth using teflon moulds of 4x4mm. The samples were then subjected to shear bond strength tests. Two-way variance analysis and Tukey HSD multiple comparison test were applied on collected data. Results: There was a significant difference between surface treatment methods used regarding shear bond strength (P<0.001). The highest shear bond strength values were detected in the "Acid" group while the lowest shear bond strength values were detected in the "control" group. On the other hand, there was no statistically significant difference among composite resins (P>0.05). Conclusions: Laser etching of the dentin tissues is not as effective as acid etching. Bulk-fill composites had similar effects compared with conventional composite resins with regard to bonding strength. More in vitro studies supported with clinical data are required to investigate the performance of bulk-fill composites and laser.